A inserção da música na educação de jovens e adultos em uma turma de ensino médio em BAGÉ/RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This work had as its theme the insertion of music on Youth and Adult Education (EJA) and your general objective was understanding the music insertion in EJA in a class of high school of a public school. As specific objectives: reflect on the articulation between teaching and research in the relationships between the Supervised Internship IV and TCC; meeting the music teaching in the context of the EJA in Bagé; meeting the profile of the students in the class and its social and musical experiences; understanding the Arts curriculum, specifically Music, in EJA. The approach of this work was qualitative character, having as a focal group methodology with students of a class of the EJA; and a semi-structured interview with the director of the institution and the teacher of the class. This work is believed to have assisted in the public understanding of the EJA, their motivations and life trajectories, as well as collaborated significantly to the field of the Music Education, and the understanding of curriculum and the inclusion of the music. It is hoped that this work will encourage other researchers to choose the EJA as lookup field, emerging new interventions to make each day more palpable music teaching for Youth and Adults.
Keywords: Inserção da música; EJA; Currículo; Ensino médio; Music insertion; Curriculum; High school; CNPQ::LINGUISTICA, LETRAS E ARTES